Participatory plant breeding: A framework for analyzing diverse approaches - Sperling, L.; Ashby, Jacqueline A.; Smith, Margaret E.; Weltzien, Eva; McGuire, Shawn (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Participatory plant breeding PPB is a relatively new approach to germplasm development. Overview summaries of cases to date show that most PPB programs were begun within the last 10 years, whether located in public-sector or nongovemment NGO crop-improvement programs. Some have argued that commercial, private-sector, plant breeding has long been c1ient-driven, or "participatory." However, when PPB is used to reach poor client groups, to breed for high-stress or heterogeneous conditions, and to incorporate diverse, specialized client preferences, the result is a fundamental change in the way plant genetic resources are managed by formal breeding programs and farmers. This paper outlines a framework for relating different participatory plant-breeding approaches lo different Outcomes .and impacts. Based on a detailed analysis of 65 case studies of programs and projects involving PPB, it suggests some of the wide variability of PPB programs and lays out key variables that are crucial for discriminating PPB approaches. These include the institutional context, the bio-social environment, the kind of participation achieved, .and the goals set for the PPB work. it is only when these variables are clearly described that practitioners can start to link the type of PPB employed method .and organizational forms with the type of impact achieved. Such clarity is essential if PPB is also to have the scientific and organizational foundations necessary lo judge its utility for a given objective.